Does status epilepticus influence the motor development of immature rats? - Kubová, H; Haugvicová, R; Suchomelová, L; Mares, P (Epilepsia, 2000)
PURPOSE: To study the effect of severe status epilepticus (SE) on the motor development of rats. METHODS: SE was induced in 12-day-old rats (P12 group) and 25-day-old rats (P25 group) using the lithium-pilocarpine model. Seizures were interrupted after 2 hours by paraldehyde with an intraperitoneal dose of 0.3 or 0.6 mL/kg, respectively. Starting 3 days after SE, all animals were repeatedly exposed to a battery of motor and behavioral tests, including the bar-holding test, rotarod test, and open field test. RESULTS: In P12 animals, motor impairment occurred 2 months after SE, when significantly worse performance in the rotarod test was found. No difference between controls and experimental rats was found in any other test used. In contrast, P25 animals were significantly poorer in the bar-holding test from postnatal day 34 until adulthood. In open field study, P25 rats were found to be hyperactive during the whole period of testing, whereas P12 animals exhibited an initial period of hypoactivity (in the first test) that was replaced by hyperactivity that lasted until 2 months of age. In the last test performed at the age of 98 days, experimental P12 animals were again less active than age-matched controls. CONCLUSIONS: Animals of both age groups exhibited permanent changes of motor performance; however, both the pattern and the time course of these changes was related to age when SE was elicited.
Keywords: Motor Skills; Animals; novorozená zvířata; Rats, Wistar; Age Factors; Status Epilepticus; status epilepticus; motorické dovednosti; pohybová aktivita; Animals, Newborn; věkové faktory; chování zvířat; Exploratory Behavior; modely nemocí na zvířatech; Pilocarpine; pilokarpin; neuroplasticita; Disease Models, Animal; krysa rodu Rattus; Behavior, Animal; Motor Activity; pátrací chování; Neuronal Plasticity; zvířata; Rats; potkani Wistar